2014
DOI: 10.1242/jcs.139394
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission is required for cardiomyocyte hypertrophy via a Ca2+-calcineurin signalling pathway

Abstract: Cardiomyocyte hypertrophy has been associated with diminished mitochondrial metabolism. Mitochondria are crucial organelles for the production of ATP, and their morphology and function are regulated by the dynamic processes of fusion and fission. The relationship between mitochondrial dynamics and cardiomyocyte hypertrophy is still poorly understood. Here, we show that treatment of cultured neonatal rat cardiomyocytes with the hypertrophic agonist norepinephrine promotes mitochondrial fission (characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
156
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 104 publications
(103 reference statements)
5
156
1
Order By: Relevance
“…A previous work reported that Ca 2+ influx through voltage-dependent Ca 2+ channels induced by high K + led to mitochondrial fission in neurons and Hela cells 22 ; a recent work demonstrated that norepinephrine induced mitochondrial fission in cultured cardiomyocytes, which was attributed to the stimulation of α1-adrenergic receptors and the consequent increase of intracellular [Ca 2+ ] i. 23 These reports were similar to the present finding in smooth muscle cells. We prechelated the cytosolic Ca 2+ with BAPTA-AM in smooth muscle cells and found that the mitochondrial fission and mito-ROS generation induced by high K + was prevented.…”
Section: Discussionsupporting
confidence: 90%
“…A previous work reported that Ca 2+ influx through voltage-dependent Ca 2+ channels induced by high K + led to mitochondrial fission in neurons and Hela cells 22 ; a recent work demonstrated that norepinephrine induced mitochondrial fission in cultured cardiomyocytes, which was attributed to the stimulation of α1-adrenergic receptors and the consequent increase of intracellular [Ca 2+ ] i. 23 These reports were similar to the present finding in smooth muscle cells. We prechelated the cytosolic Ca 2+ with BAPTA-AM in smooth muscle cells and found that the mitochondrial fission and mito-ROS generation induced by high K + was prevented.…”
Section: Discussionsupporting
confidence: 90%
“…In the endocrine pancreas of mice exposed to a high-fat diet, metabolic changes associated to hypertrophy were found to be more accentuated in males (85). Alterations in processes related to mitochondrial biogenesis also play a role in hypertrophy (90). Interestingly, these processes can be differentially regulated by female and male sex hormones (91).…”
Section: Figmentioning
confidence: 99%
“…It has been demonstrated that NE promotes mitochondrial fission leading to a decrease in the mitochondrial mean volume and an increase in the relative number of mitochondria per cell in rat neonatal cardiomyocytes (Pennanen et al 2014). However, in contrast to pig pinealocytes, NE acts on cardiomyocytes through alpha 1 -adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are associated with changes in cell metabolism, cell development, and cell death. They are also involved in the transmission of signaling messengers and the exchange of metabolites within the cell (Chada and Hollenbeck 2003, Kuzmicic et al 2011, Pennanen et al 2014. Changes in mitochondrial morphology can consequently affect the functioning of the respiratory chain, the regulation of the mitochondrial permeability transition pore, and the interaction with other organelles (Piquereau et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation